Best Answer

11 + 6k = 65

Subtract 11 from both sides:

6k = 65-11

6k = 54

Divide by 6 to get k:

k = 54/6

k = 9

Study guides

☆☆

Q: 11 plus 6k equals 65

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

8k = 6k - 26 8k - 6k = 6k - 6k - 26 2k = -26 2k / 2 = -26 / 2 k = -13. The answer is k = -13.

-6k+7k = 1k or normally k on its own.

The answer is 13k .

7k + 4 + 4k - 9 - 5k (7k + 4k - 5k) + (4 - 9) 6k + -5 6k - 5

4k + 24 = 6k - 10 subtract 4k from each side 4k - 4k + 24 = 6k - 4k - 10 24 = 2k - 10 add 10 to each side 10 + 24 = 2k - 10 + 10 34 = 2k divide each side integers by 2 17 = k ------------check 4(17) + 24 = 6(17) - 10 68 + 24 = 102 - 10 92 = 92 checks

Related questions

k + 6k - 13 = 177k = 30k = 30/7k = 4.2857

Same as subtracting 6 from 7 = K

-47 + 6k = 3k - 2Add 47 to each side:6k = 3k +45Subtract 3k from each side:3k = 45Divide each side by 3:k = 15

-47 + 6k = 3k - 2Add 47 to each side:6k = 3k +45Subtract 3k from each side:3k = 45Divide each side by 3:k = 15

-6K+7K=1K or K

8k = 6k - 26 8k - 6k = 6k - 6k - 26 2k = -26 2k / 2 = -26 / 2 k = -13. The answer is k = -13.

6k + 21 = 36k + 21 - 21 = 3 - 216k = -186k/6 = -18/6k = -3A check to make sure this is right:6(-3) + 21 = 3-18 + 21 = 33 = 3Yes, this is correct.

-6k + 7k = k

1k

19k

given: 4w+(6k-3w)+(2-k)remove parentheses: 4w+6k-3w+2-kcollect like terms: 4w-3w+6k-k+2simplify: w+5k+2

-6k+7k = 1k or normally k on its own.